Prevalence of neutropenia in the U.S. among reproductive-aged women: a population-based analysis of NHANES 2013–2020 - Junfeng Chen; Shuangna Song; Yiran Li (BMC Public Health)
Abstract Background Infertility is one of the prominent public health concerns nationwide. Neutrophils, despite their established significance as vital players in both inflammatory and immune processes, have been studied scarcely in terms of their effect on female infertility. The present study aimed to determine the prevalence of neutropenia among women of reproductive age in the U.S. to contribute valuable insights to the broader context of reproductive health. Methods The present study was designed as a cross-sectional investigation. The data of 5,250 female participants aged 18–45 years were obtained from the National Health and Nutrition Examination Survey (NHANES) conducted between the years 2013 and 2020. The representativeness of the population was ensured by conducting statistical assessments based on NHANES weights. A logistic regression model was established to assess the hematologic parameters across the distinct populations stratified according to age, ethnicity, smoking status, and infertility. Multivariate logistic regression was performed next, and weighted odds ratios along with the 95% confidence interval values were calculated, which assisted in predicting the prevalence of neutropenia among the female participants. Results The data of a total of 5,250 female participants, representing a multiracial population of 51.17 million in the United States, were analyzed in the present study. Meanwhile, the estimated neutropenia incidence was 7.09% (95% CI: 6.16−8.01%), which indicated a prevalence among approximately 36.2 million U.S. citizens. In comparison to white subjects, black subjects exhibited a significantly lower average leukocyte count, with a mean difference (MD) of 1.16 × 109/L (P < 0.001), along with a lower neutrophil count (MD: 1.09 × 109/L; P < 0.001). It is noteworthy that a substantial decrease was noted in the distribution graphs of both neutrophil and leukocyte counts among the black subjects. Moreover, compared to non-smokers in the racial populations, including white, Mexican American, and black people, the smokers exhibited significantly elevated mean leukocyte count and mean neutrophil count. The logistic regression analysis indicated an elevated risk of neutropenia among black individuals and females with infertility. Conclusions Neutropenia appears to have a higher prevalence in the general population compared to that acknowledged previously. The findings of the present study indicated association between neutropenia and infertility. This highlighted the importance of directing increased attention toward neutropenia in the context of both research and clinical practice.